Preparation, characterisation and entrapment of a non-glycosidic threitol ceramide into liposomes for presentation to invariant natural killer T cells. - Kaur, R; Chen, J; Dawoodji, A; Cerundolo, V; Garcia-Diaz, Y; Wojno, J; Cox, L; Besra, G; Moghaddam, B; Perrie, Y (2011)
Dendritic cells (DCs) are able to present glycolipids to invariant natural killer T (iNKT) cells in vivo. Very few compounds have been found to stimulate iNKT cells, and of these, the best characterised is the glycolipid α-galactosylceramide, which stimulates the production of large quantities of interferon-gamma (IFN-γ) and interleukin-4 (IL-4). However, αGalCer leads to overstimulation of iNKT cells. It has been demonstrated that the αGalCer analogue, threitol ceramide (ThrCer 2), successfully activates iNKT cells and overcomes the problematic iNKT cell activation-induced anergy. In this study, ThrCer 2 has been inserted into the bilayers of liposomes composed of a neutral lipid, 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC), or dimethyldioctadecylammonium bromide (DDA), a cationic lipid. Incorporation efficiencies of ThrCer within the liposomes was 96% for DSPC liposomes and 80% for DDA liposomes, with the vesicle size (large multilamellar vs. small unilamellar vesicles) making no significant difference. Langmuir-Blodgett studies suggest that both DSPC and DDA stack within the monolayer co-operatively with the ThrCer molecules with no condensing effect. In terms of cellular responses, IFN-γ secretion was higher for cells treated with small DDA liposomes compared with the other liposome formulations, suggesting that ThrCer encapsulation in this liposome formulation resulted in a higher uptake by DCs.